(untitled) (Psychology Travelogs, 2025)
The article carries out a theoretical study of factors that influence the development of motivation for educational activities and stress resistance in students. Certain features of the orientation of the personality, conditions of upbringing that significantly affect the formation of a positive attitude of students to educational activities are identified. The system of factors that influence students’ attitude to learning is analyzed. Objective factors that influence the attitude to educational activities are identified, which are simultaneously stressor factors for students: pedagogical influence, interpersonal interaction, incentive factors, the system of activities in a higher education institution. Subjective factors are identified, which include: satisfaction with the chosen specialty, civic position, level of achievement in educational activities, etc. It is noted that an important factor that influences the attitude to educational activities is such a property of the personality as stress resistance. Factors that provoke the development of stress in educational activities are analyzed. It has been proven that students’ stress resistance in educational activities is a complex property of the personality, characterized by the necessary adaptation of the student to the influence of external and internal factors in the process of educational activities and includes such personal components as low personal and situational anxiety, low level of neuropsychic tension, adequate self-esteem, high work capacity, emotional stability, which ensures the successful achievement of the goal of the activity and is implemented in the cognitive, emotional, motivational and behavioral spheres of the personality.